(untitled) (PALIMPSEST / ПАЛИМПСЕСТ, 2026)
The new monograph by R. Mudrochová presents a phenomenon that has been largely neglected in systemic linguistic studies. However, the strong discursive visibility of lexical blends has led the author to compile a corpus of 286 lexical items, which were subjected to a detailed multi-stage analysis (Mudrochová, 2025: 94). The author also demonstrates that, in many cases, these lexical creations serve as substitutes for Anglicisms (Mudrochová, 2022). Consequently, the publication Les amalgames lexicaux en français contemporain. Analyses, contextes, emplois (245 pages), published in Prague by Karolinum, represents a major contribution to this field. It argues that the blend word (mot-valise) has become the most productive blending process in contemporary French, both quantitatively and discursively. The author’s ambitious aim is to fill a gap in systemic theoretical studies devoted to lexical blends and to restore their full scientific legitimacy. From a methodological perspective, the study relies on digital resources rich in lexical blends.